Platelet-Rich Fibrin in Periodontal Treatment and Implant Dentistry: A Narrative Review: PRF in Periodontal and Implant Treatment - Khodabandelu, Asal; Atarbashi-Moghadam, Fazele (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Platelet-rich fibrin (PRF) is a second-generation platelet derivative characterized by a dense fibrin network enriched with cytokines and growth factors. Its preparation includes involves centrifugation of autologous blood without anticoagulants that form a concentrated fibrin matrix, which could be inserted directly into the site of injury or used as a membrane for specific applications. Higher concentrations of growth factors in PRF lead to faster periodontal regeneration and higher clinical attachment gain, along with new bone formation. Thus, it’s widely used in periodontal treatment. PRF has also shown promising results in implant dentistry. This review aims to summarize the current knowledge concerning the applications of PRF in periodontal treatment and implant dentistry and highlight its potential to improve clinical outcomes in these fields.